Approaching ’Home’ in Bharati Mukherjee’s Darkness - Crespo Gómez, Ana María (International Journal of English Studies, 2022)
The object of this study is to explore the relationship between ’home’ and the decline of ethnic identity in the female characters of Bharati Mukherjee’s collection of short stories Darkness (1985). This paper argues that while it is generally accepted that diaspora entails a questioning of a sense of belonging (Kennedy, 2014: 12), for Bharati Mukherjee, "the price that the immigrant willingly pays, and that the exile avoids, is the trauma of self-transformation" ("Two ways to belong in America", 1996). This article seeks to contextualize the Indian diaspora in its roots and routes, proving an inextricable link with gendering of the concept of ’home’ in Bhattacharjee (1996). The introduction is underpinned by a theoretical framework on diaspora namely South Asian female migrants in the United States, and an analysis of the Indian concept of nation, from which the literary assessment departs.